Political education in Georgia: Analysis and Challenges of the Current Situation - Manvelidze, Irakli; Zoidze, Ineza; Lazba, Natalia (Politics / პოლიტიკა, 2018)
After the restoration of the state independence of Georgia in the field of social sciences, the attitude and assessment of political education has changed. Despite the reliance on ideology and academic disciplines, including the principles of policy sciences, their development in line with formal or informal rules that stand far from real institutionalization frameworks. Moreover, the latter acquired sharply differentiated and less regular character. One of the most challenging tasks in the general public is the revival of the structure, content and learning methods of political education. To change not only the list and methods of political education, but also the science of science facing a difficult task to ensure the formation of ideas and ideas that are respond well to the achievements of the world civilization, the fair state and the development of civil society.